1999
DOI: 10.1002/j.2161-1920.1999.tb01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Job Seeking Frequency and Psychological Well‐Being in the Unemployed

Abstract: Unemployed (n = 118) and employed (n = 120) people were contrasted on variables of well‐being, confidence, and employment commitment. The unemployed scored lower on the General Health Questionnaire (Goldberg, 1972) and the General Self‐Efficacy Scale (Sherer et al., 1982). No differences were Identified on levels of employment commitment. For the unemployed sample, predictors of job‐seeking behavior and well‐being were then examined. Intention to seek work predicted job‐seeking behavior, while self‐efficacy, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
4
19
0
2
Order By: Relevance
“…Evidence suggests that even average performing interns are more likely to receive job offers than students who did not complete internships (Gault et al, 2010). Thus previous work experience through internships gives new graduates a competitive advantage because they are exposed to real working conditions Professional confidence Chowdhury et al (2002), Wiener et al (1999), Knouse et al (1999) 21/30 A high level of self-confidence is linked directly to performance, such that higher levels of perceived confidence lead to a more effective individual (Wiener et al, 1999).…”
Section: Academic Reputationmentioning
confidence: 99%
“…Evidence suggests that even average performing interns are more likely to receive job offers than students who did not complete internships (Gault et al, 2010). Thus previous work experience through internships gives new graduates a competitive advantage because they are exposed to real working conditions Professional confidence Chowdhury et al (2002), Wiener et al (1999), Knouse et al (1999) 21/30 A high level of self-confidence is linked directly to performance, such that higher levels of perceived confidence lead to a more effective individual (Wiener et al, 1999).…”
Section: Academic Reputationmentioning
confidence: 99%
“…Job search intention in turn acts as the immediate antecedent of job search behaviour. The unemployed that are highly committed on employment will display an intensive job search behaviour (Wiener, Oei, & Creed, 1999) because they are probably the most affected by their unemployment. An intensive search for a new job increases the chances of finding one (Kanfer et al, 2001), reduces the risk of long-term unemployment (McKee-Ryan et al, 2005), leads to higher levels of psychological and physical well-being (Feather, 1990;McKee-Ryan et al, 2005;Paul & Moser, 2006) and increases the satisfaction with the new job (Leana & Feldman, 1988).…”
Section: Experience Of Unemployment Attitudes Towards Employment Andmentioning
confidence: 99%
“…Career decision‐making self‐efficacy—an individual's beliefs about his or her capability to perform tasks related to the career decision‐making process (Taylor & Betz, 1983)—has been shown to be related to several career‐related constructs, including certainty (Betz, Klein, & Taylor, 1996) and fear of commitment (Betz & Sterling, 1993), in addition to the personality traits of conscientiousness and extraversion (Bullock‐Yowell, Andrews, & Buzzetta, 2011; Hartman & Betz, 2007). Self‐efficacy has been seen as an important factor to address with unemployed individuals (Steinweg, 1990) and acknowledged in research on the unemployed (e.g., Aviram, 2006; Wiener et al, 1999). In Germany, Pinquart, Juang, and Silbereisen (2003) found that individuals with higher self‐efficacy beliefs and academic scores were less likely to become unemployed and were more likely to experience job satisfaction.…”
Section: Thinking Self‐efficacy and Interestsmentioning
confidence: 99%
“…Unemployment is at a record high in the United States, yet researchers and practitioners do not have a comprehensive understanding of the career development of the unemployed adult (Donohoe & Patton, 1998). A review of the literature revealed a sparse selection of research involving unemployed participants as it related to job skills training (Tango & Kolodinsky, 2004), general career guidance (Donahoe & Patton, 1998), and psychological well‐being (Wiener, Oei, & Creed, 1999).…”
mentioning
confidence: 99%